2018
DOI: 10.1002/ep.13049
|View full text |Cite
|
Sign up to set email alerts
|

Carbon emissions, diverse energy usage and economic growth in south africa: Investigating existence of the environmental kuznets curve (EKC)

Abstract: This article examined the relationships involving carbon emissions, economic growth and energy consumption by employing the environmental Kuznets curve (EKC) in South Africa from 1980 to 2014. The auto regressive distributed lag approach and Johansen cointegration tests proved that the variables are cointegrated. The article findings show that combined (total energy consumption) and hydrocarbon gas and petroleum consumption demonstrates evidence of EKC in the long‐run. Other separated data (primary coal, secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 43 publications
5
24
0
Order By: Relevance
“…(1) and the selection of explanatory variables are based on the existing literature (Ganda, 2019;Liu et al, 2017;Sugiawan & Managi, 2016;Zoundi, 2017). The quadratic specification of income level is extensively used in research related to the EKC hypothesis of the income-emissions relationship.…”
Section: Model Specificationmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) and the selection of explanatory variables are based on the existing literature (Ganda, 2019;Liu et al, 2017;Sugiawan & Managi, 2016;Zoundi, 2017). The quadratic specification of income level is extensively used in research related to the EKC hypothesis of the income-emissions relationship.…”
Section: Model Specificationmentioning
confidence: 99%
“…Many studies have found an association between CO 2 emissions and income level (Apergis & Ozturk, 2015;Boutabba, 2014;Ganda, 2019;Jalil & Feridun, 2011;Kais & Sami, 2016;Ozturk & Acaravci, 2013;Shahbaz et al, 2019). These studies generally provide evidence of an inverted U-shape relationship, the environmental Kuznets curve (EKC) hypothesis, in which CO 2 emissions increase with an increase in the income level until reaching a threshold level, and decline as the income level continues to surge beyond the threshold level.…”
Section: Introductionmentioning
confidence: 99%
“…Many other studies, on the other hand, failed to demonstrate such a relationship and argued that the hypothesis is not valid. 3036…”
Section: Introductionmentioning
confidence: 99%
“…OECD (2019c) also confirms that most OECD economies managed to meet their emission targets as per the Kyoto protocol spanning 2008 to 2020 and therefore on course to meet reduction targets for 2020. On that note, studies to survey economic growth and emissions have also heightened (Dogan & Turkekul, 2016; Ganda, 2019a, 2019b, 2019c; Pata, 2018; Seker, Ertugrul, & Cetin, 2015; ). In this vein, evidence shows that the environmental Kuznets curve (EKC) hypothesis is also the most investigated hypothesis as it describes the association between pollution and GDP level because the impact of economic practices on the natural environment has heightened and hence attracted greater attention from green stakeholders (Ganda, 2019c).…”
Section: Introductionmentioning
confidence: 99%
“…In this vein, evidence shows that the environmental Kuznets curve (EKC) hypothesis is also the most investigated hypothesis as it describes the association between pollution and GDP level because the impact of economic practices on the natural environment has heightened and hence attracted greater attention from green stakeholders (Ganda, 2019c). The EKC posits that pollution is heightened as economic development increases and decreases after a particular threshold of wealth has been attained (Ganda, 2019b).…”
Section: Introductionmentioning
confidence: 99%